Molecular imaging based biophysical changes of striatum closely associated with cognitive impairment in childhood self-limited epilepsy with centrotemporal spikes. - Yu, Congcong; Wang, Jing; Jin, Chentao; Hu, Daoyan; Dou, Xiaofeng; Zhang, Xiaohui; Sun, Yuan; Qian, Shufang; Yao, Qiong; Feng, Jianhua; Zhong, Yan; Tian, Mei; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: This study aimed to investigate the functional role of striatum in cognitive impairment of self-limited epilepsy with centrotemporal spikes (SeLECTS) patients using 18F-fluorodeoxyglucose ([18F]FDG) positron emission tomography (PET) and structural magnetic resonance imaging (sMRI). Methods: Forty-three patients with SeLECTS (24 typical and 19 atypical) who underwent [18F]FDG PET/CT, 3D-T1WI MRI and neuropsychological assessment were prospectively enrolled. Twenty children with extracranial tumors and twenty healthy children were included as the PET control and MRI control, respectively. Glucose metabolism of brain regions was obtained by measuring standardized uptake value ratio (SUVR) of PET images. Brain structural alterations were derived from MRI image by measuring nuclei volume. Correlation analysis was performed to investigate the relationship among glucose metabolism, brain structural alterations and cognitive function. Results: Compared with typical SeLECTS and control group, atypical SeLECTS patients had inferior intelligence quotient (IQ). PET image analysis presented significantly reduced SUVR in bilateral putamen and pallidum of SeLECTS patients. Specifically, atypical SeLECTS had the lowest SUVR of bilateral putamen and pallidum. MRI image analysis showed markedly reduced volume of left putamen and bilateral pallidum in atypical SeLECTS and enlarged volume of left pallidum in typical SeLECTS. Correlation analysis showed that altered SUVR and volume in lenticula were significantly associated with cognitive impairment. Conclusion: This study presented the first imaging findings that cognitive impairment in both atypical and typical SeLECTS patients is highly correlated with glucose metabolism and volume of lenticula, especially in the pallidum, providing further understanding for cognitive impairment of SeLECTS.